STRATEGIC MANAGEMENT OF ISLAMIC EDUCATIONAL INSTITUTIONS IN THE NEW NORMAL ERA - Pramitha, Devi (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
Today the educational environment is experiencing a very competitive development where it requires educational institutions, especially Islamic education institutions to build more excellence and update the roadmap in a sustainable manner, take strategic steps and mobilize the capabilities and commitment of all organizational members in realizing the future of Islamic educational institutions. Currently the world of education is preparing to enter a new normal era, school management and learning activities will definitely change. There is new management, new habits, new learning interactions that will mark a new normal era in the world of education. Therefore, Islamic education institutions must develop new strategy management so that they can survive and compete in the current New Normal era. This study uses a qualitative approach with literature study methods. From the results of the author's analysis, it can be concluded that: (1) Islamic education institutions in the current New Normal era is to review the vision and mission to be achieved; (2) The second is to identify the resources that need to be owned and procured; and (3) The third strategy is the creative and innovative execution of change steps through collaboration with various partnerships or other external parties who care about education.